MENINGKATKAN KEMAMPUAN MEMBACA DAN MENULIS PERMULAAN SISWA KELAS II SDN SP4 KOBE KULO DENGAN MENGGUNAKAN METODE COOPERATIVE INTEGRATED READING AND COMPOSITION PADA TEMA 6 SUBTEMA 1 HEWAN DI SEKITARKU - Sumar A Latif; Ridwan Jusuf; Asri S Tamalene (PEDAGOGIK, 2023)
This study aims to determine the increase in the ability of Class II students at SDN SP4 Kobe Kulo in reading and writing beginning in Theme 6 Sub-theme 1 Animals Around Me through the Cooperative Integrated Reading and Composition (CIRC) learning method,This type of research is class action research (Class Room Action Research). The PTK design in this study uses the Kemmis and McTaggart model which includes four steps, namely (1) action planning; (2) implementation of actions; (3) observation; and (4) reflection. This research was conducted in class II of SD Negeri SP4 Kobe Kulo with an allocation of 2 months for data collection, starting from April 2022 – June 2022. The data collection techniques used were observation, documentation and testing techniques. Data analysis techniques using descriptive statistical analysis.The results showed that: (1) The ability of class II students at SDN SP4 Kobe Kulo in reading and writing at the beginning had increased after using the CIRC method. In cycle I, the average ability of students who achieved mastery in learning to read was 8 out of 15 people or 53.33% in the less category. While the students' writing ability achieved learning mastery as much as 9 out of 15 people or 60% in the sufficient category. In cycle II, 13 out of 15 students who achieved mastery in learning to read or 86.66% were in the very good category. As for the students' writing ability, 13 out of 15 people or 86.66% of the very good category achieved learning mastery.